PERSONAL COMPUTER SOFTWARE. - Matchonov Akmal (The latest pedagogical and psychological innovations in education, 2025)
Personal computer software is a set of programs that help users perform various tasks. This software includes operating systems, office programs, multimedia applications, security programs, Internet browsers, games and many other applications. When creating software for personal computers, the main consideration is user convenience, efficiency and security.